النظام القانوني للوزير الأول في ظل التعديل الدستوري الجديد - لبنى سرايعية; عتيق هاجر (My University, 2018)
Summary: The position of First Minister as Second Pole in the Executive Power, is not an innovation of the system. Algerian constitutionalism, it has been transmitted by a number of comparative regimes: France, Egypt. Despite the reforms known in Algeria's constitutional system, which began in 1989 and were devoted to At the level of executive authority, however, this has maintained the nature of the existing political system to the effective control of the President of the Republic, and thus contrary to what the articles of the Constitution suggest From adopting duality about executive power, but it was formalized and high, replacing The position of Head of Government as First Minister is not just a formal replacement, it represents In fact, it is a fundamental change in the powers of the First Minister, who was not granted the amendment The Constitution (2016) is only a few prerogatives, most of which are completed only with the prior approval of the President. This is a staffed audience. On the organic side is the absolute dependence of the First Minister and members of the Government on the President. The Democratic People's Republic of Korea, arguing that the absence of independence and equality are significant features of the relationship Between the First Minister and the President of the Republic, which made the First Minister fully dependent The President of the Republic continues to lose his true meaning. In addition to the foregoing, the Algerian Constitution has violated an important rule and is in conjunction. Authority with Responsibility The First Minister became a political official without any corresponding authorities Accountability, this option is double accountability to both the President of the Republic and the Parliament. He must have the confidence that he has the power to appoint and isolate him, as well as the confidence of Parliament to be in front of The National People's Assembly and the National Assembly through government oversight of its functions. Finally, we have reached a set of conclusions and recommendations, which we hope will be taken into account in the future. These proposals enable us to strengthen and strengthen the position of the First Minister in the constitutional order. Algeria gives him active powers without interfering in the powers of the President of the Republic. ........................... ملخص: إن منصب الوزیر الأول كقطب ثاني في السلطة التنفیذیة، لیس ابتكار من وحي النظام الدستوري الجزائري، بل تناقلته العدید من الأنظمة المقارنة منھا: فرنسا ، مصر. رغم الإصلاحات التي عرفھا النظام الدستوري الجزائري ابتدأ من سنة 1989 وتكریس الثنائیة على مستوى السلطة التنفیذیة، إلا أن ذلك أبقى على طبیعة النظام السیاسي القائم على السیطرة الفعلیة لرئیس الجمھوریة، وبالتالي فإنه خِلافًا لِما توحي به مواد الدستور من تبني الازدواجیة بخصوص السلطة التنفیذیة، إلا أنھا كانت شكلیة وعلیه فإن استبدال منصب رئیس الحكومة بمنصب الوزیر الأول لیس مجرد استبدال شكلي فقط، وإنما یمثل في حقیقة الأمر تغییرا جوھریا في صلاحیات الوزیر الأول، الذي لم یمنحه التعدیل الدستوري( 2016 ) إلا القلیل من الصلاحیات و التي لا یتم أغلبھا إلا بموافقة مسبقة لرئیس الجمھوریة ھذا من الناحیة الوظیفیة . أما من الناحیة العضویة تتمثل في التبعیة المطلقة للوزیر الأول وأعضاء الحكومة لرئیس الجمھوریة، مما یدعو للقول أن غیاب الاستقلالیة والمساواة ھما میزتان بارزتان للعلاقة بین الوزیر الأول ورئیس الجمھوریة، الأمر الذي جعل الوزیر الأول في علاقة تبعیة تامة ومستمرة لرئیس الجمھوریة مما جعل مبدأ ثنائیة السلطة التنفیذیة یفقد معناه الحقیقي. بالإضافة إلي ما سبق نجد أن النظام الدستور الجزائري أخل بقاعدة ھامة وھي تلازم السلطة مع المسؤولیة حیث أصبح الوزیر الأول مسؤول سیاسیا دون أي سلطات تقابل تلك المسؤولیة، وتعتبر ھذه الخیرة مسؤولیة مزدوجة أمام كل من رئیس الجمھوریة والبرلمان. حیث یجب أن ینال ثقته الذي یملك سلطة تعینه وعزله وكذلك ثقة البرلمان حیث تكون أمام المجلس الشعبي الوطني ومجلس الأمة من خلال رقابة الحكومة لمھامھا . وفي الأخیر توصلنا إلي مجموعة من النتائج والتوصیات ونأمل أن یؤخذ بھا في المستقبل حیث تمكننا ھذه المقترحات من تعزیز وتقویة مكانة الوزیر الأول في النظام الدستوري الجزائري و تمنحه سلطات فاعلة دون تدخلھا في سلطات رئیس الجمھوریة . ...................... Résumé: La position du Premier ministre en tant que deuxième pôle du pouvoir exécutif n'est pas une invention inspirée par le système constitutionnel algérien, mais elle a été relayée par plusieurs systèmes comparatifs, dont la France et l'Egypte. Malgré les réformes définies par le système constitutionnel algérien à partir de 1989 et l'instauration du bilatéralisme au niveau de l'exécutif, cela a préservé la nature du système politique basé sur le contrôle effectif du Président. Le remplacement du poste de Premier ministre par le poste de Premier ministre n'est pas simplement un remplacement formel, mais constitue en fait un changement fondamental dans les pouvoirs du Premier ministre, que l'amendement constitutionnel (2016) lui a conféré peu d'autorité, En avance sur le président de la République en termes de fonctionnalité. Le côté organique est la subordination absolue au premier ministre et les membres du gouvernement du Président de la République, qui appelle à dire que le manque d'indépendance et d'égalité sont deux avantages saillants de la relation entre le Premier ministre et le Président de la République, qui a fait le premier ministre subordination complète et relation continue au Président de la République, ce qui rend le principe de pouvoir exécutif bilatéral Perd sa vraie signification. En plus de ce qui précède, nous constatons que la constitution algérienne viole une règle importante, celle du Premier ministre, où le Premier ministre est politiquement responsable sans aucune autorité pour assumer cette responsabilité, ce qui est une double responsabilité pour le président et le parlement. Là où il faut avoir confiance, qui a le pouvoir de le nommer et de l'isoler ainsi que la confiance du Parlement où il est devant l'Assemblée populaire nationale et le Conseil de la nation à travers le contrôle du gouvernement de ses fonctions. Dans la dernière, nous sommes arrivés à un ensemble de conclusions et recommandations, et nous espérons être prises à l'avenir où ces propositions nous permettront d'améliorer et de renforcer la position du Premier ministre dans l'ordre constitutionnel algérien et lui donner des pouvoirs efficaces sans ingérence dans les pouvoirs du Président.